Musings During a Symposium Afternoon - David A. Lander (Washington University Law Quarterly, 1994)
In this brief musing I will describe one of the many bases for concluding that when one tracks through current American bankruptcy law, she finds that there is a series of principles that overshadow the law and economics principles. I will then compare the process by which bankruptcy law is made in the United States with the process by which Article 9 of the Uniform Commercial Code is made, to show that bankruptcy is an area in which Congress must strike a balance more toward the middle of the political spectrum than the law and economics people would choose.
Keywords: Bankruptcy law; United States; Bankruptcy; Law & economics